Increased Rates of Mild Traumatic Brain Injury among Older Adults in US Emergency Departments, 2009-2010: Mild Traumatic Brain Injury in Older Adults - Albrecht, Jennifer S. (J Head Trauma Rehabil, 2016)
OBJECTIVE: Estimate rates of emergency department (ED) visits for mild traumatic brain injury (TBI) among older adults. We defined possible mild TBI cases to assess underdiagnoses. DESIGN: Cross-sectional SETTING: National sample of ED visits 2009-2010 captured by The National Hospital Ambulatory Medical Care Survey. PARTICIPANTS: Aged 65 and older MEASUREMENTS: Mild TBI defined by ICD-9-CM codes (800.0x-801.9x, 803.xx, 804.xx, 850.xx-854.1x, 950.1x-950.3x, 959.01) and a Glasgow Coma Scale score ≥14 or missing, excluding those admitted to the hospital. Possible mild TBI was defined similarly among those without mild TBI and with a fall or motor vehicle collision as cause of injury. We calculated rates of mild TBI and examined factors associated with diagnosis of mild TBI. RESULTS: Rates of ED visits for mild TBI were 386/100,000 among those 65-74; 777/100,000 among those 75-84; and 1,205/100,000 among those >84. Rates for women (706/100,000) were higher than for men (516/100,000). Compared to possible mTBI, diagnosis of mild TBI was more likely in the West (OR 2.31; 95%CI 1.02, 5.24) and less likely in the South/Midwest (OR 0.52; 95%CI 0.29, 0.96) than in the Northeast. CONCLUSIONS: This study highlights an upward trend in rates of ED visits for mild TBI among older adults.